Modeling of New Three-Phase High Voltage Power Supply For Industrial Microwave Generators With One Magnetron Per Phase - El Ghazal Naama; M. Chraygane; M. Ferfra; A. Belhaiba; M. Fadel; B. Bahani (International Journal of Electrical and Computer Engineering (IJECE), 2013)
This original work treats the feasibility study of a new HV power supply with a three-phase character, supplying a magnetron 800 Watts-2450 MHz per phase, for industrial microwave generators from the modeling with the EMTP code of a single-phase HV power supply for one magnetron. The exploitation of the modeling, with EMTP code, of the power system for one magnetron is to use, essentially, the developed model of its transformer, which is a π quadruple, consisting of saturable inductances able to translate the non-linear phenomena of saturation, while guaranteeing the stabilization process of the magnetron current. Using the new power supply device with a three-phase character and the EMTP code, the feasibility study, in nominal mode, of the three-phase power supply was performed satisfactory. The analysis of the results obtained helped to confirm the possibility of functioning of this new system without interaction between magnetrons, which provides, relative to the current device, gains of size, volume, cost of implementation and maintenance and makes this new system more economical, while guaranteeing the regulation process of the current in each magnetron.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2409